Carbon capture and storage in branching stage alfalfa (Medicago sativa L.) by 13C pulse labeling. (27th April 2017) - Man, Jing; Deng, Bo; Yang, Shichao; Yang, Fuyu
Abstract: In the present study, we investigated the absorption and transfer of photosynthetic carbon among the different alfalfa parts. Alfalfa was planted under controlled conditions and pulse‐labeled with carbon–13 dioxide ( 13 CO2 ; gas) during its branching stage. Then, the amounts of 13 CO2 on the alfalfa leaves, stems and roots were measured, and soil samples were taken after 6, 12, 18, 24 and 30 days. The carbon‐13 ( 13 C) distribution ratios of roots, stems and leaves increased over the sampling time and reached the maximum value at day 18; after that, the values decreased but still higher than day 6 and day 12. The 13 C distribution ratio in the roots increased gradually to 2.77% at day 30. Over the extended labeling time, 13 C loss caused by root and microbial respiration increased. There was no clear trend visible in the 0–10 cm soil layer, but in the 10–20 cm soil layer, the 13 C distribution ratio increased gradually from 2.46% at day 6 to 3.05% at day 30. The 13 C content in the 0–10 cm soil layer at days 6, 12, 18, 24 and 30 after labeling ranged from 0.90 ppm to 1.53 ppm and in the 10–20 cm layer increased from 0.83 ppm (6 days) to 1.12 ppm (30 days). The 13 CO2 released by microbial respiration increased gradually from 2.02 mg at day 6 to 23.30 mg at day 30. The 13 CO2 content released by alfalfa root respiration accounted for the majority of total respired 13 C content and increased from 24.06 mg (6 days) to 54.15 mg (18 days) and remained constant hereafter. This study suggests that carbon was rapidly cycled between the different parts of alfalfa and soil by means of photosynthesis and respiration. The results obtained in this study will be of importance for building the mechanistic model of photosynthetic carbon flow in alfalfa‐soil system.